Development of an Excel-based tool for seamless resource planning of a mid-size company - Tan, Dennis Yi Xuan (Nanyang Technological University, 2020)
Manufacturing Planning and Control (MPC) is critical for effective management and improving the overall production efficiency of companies. The manufacturing environment is complex with different data sources across different teams from the same company. An effective MPC system is therefore important as it coordinates the company’s supply chain. The system also enables informed decision making throughout the entire chain which, in turn, speeds up response times and minimises inefficiencies. However, these MPC tools have been very expensive due to their complexity. A system from Oracle cost companies USD$12,000 per user per year (Oracle, 2020). Even the less complex MPC tools that simply allow companies to carry out demand forecasting and production planning can cost USD$600 per user per year (MRPeasy, 2020). This report presents an Excel-based tool that allows forecasting, Sales & Operations planning, Master Production Scheduling, and Material Requirements Planning for the same data seamlessly and in an integrated manner. Moreover, this tool was built to model the operational requirements of an actual company, Zurn Wilkins, which manufactures water control products for plumbing. Besides being used by SMEs for their resource planning, such a tool can also be an educational tool for students of Manufacturing Planning and Control functions.